Protein Crystallography and Site‐Direct Mutagenesis Analysis of the Poly(ethylene terephthalate) Hydrolase PETase from Ideonella sakaiensis. (28th May 2018) - Liu, Bing; He, Lihui; Wang, Liping; Li, Tao; Li, Changcheng; Liu, Huayi; Luo, Yunzi; Bao, Rui
Abstract: Unlike traditional recycling strategies, biodegradation is a sustainable solution for disposing of poly(ethylene terephthalate) (PET) waste. PETase, a newly identified enzyme from Ideonella sakaiensis, has high efficiency and specificity towards PET and is, thus, a prominent candidate for PET degradation. On the basis of biochemical analysis, we propose that a wide substrate‐binding pocket is critical for its excellent ability to hydrolyze crystallized PET. Structure‐guided site‐directed mutagenesis revealed an improvement in PETase catalytic efficiency, providing valuable insight into how the molecular engineering of PETase can optimize its application in biocatalysis. Abstract : Waste not, want not : Biodegradation is a sustainable solution for poly(ethylene terephthalate) (PET) waste disposal. PETase, a newly identified enzyme from Ideonella sakaiensis, has high efficiency and specificity towards PET and is thus a promising candidate for PET degradation. Structure analysis of the PETase reveals that its shallow and broad pocket is critical for the degradation of aggregated PET.